Tranexamic Acid in Patients with Green Snake Bite in Western Region of Nepal - Sapkota, Subash; Acharya, Ramesh Raj; Paudel, Navaraj (Birat Journal of Health Sciences, 2018)
Introduction: Green snakes found in hilly areas of Nepal cause significant morbidity in form of local swelling and bleeding manifestations. Polyvalent antivenoms are not indicated for the treatment. Specific management protocols are not endorsed for its bite. Conventionally, vitamin K and fresh frozen plasma are used to correct deranged coagulation in green snake bite. Objectives: The objective of this study was to evaluate the effectiveness of addition of tranexamic acid to the conventional method in green snake bite in western region of Nepal. Methodology: A hospital based, prospective comparative cross-sectional study was conducted at Department Medicine Manipal Teaching Hospital, Pokhara, Nepal from April 2014 to October 2017. It included 110 patients aged 15 to 76 years of both genders with confirmed history of green snake bite. Participants were alternately randomized into two groups; conventional group, tranexamic acid group. Duration of hospital stay was considered the primary outcome measure for this study while INR levels were considered the secondary outcome measure. Data were collected in a preformed pro forma and analyzed using SPSS version 16.0. Differences were considered significant if p-value is < 0.05. Results: The age (mean: 35.41; SD=17.23) of the study population ranged from 15 -76 years. The median duration of hospital stay in conventional group was 8 days (Inter Quartile Range = 7 to 8) and in tranexamic acid group was 6 days (Inter Quartile Range: 5 to 6). Mean INR was statistically significantly different at day 5 and day 6 in favor of tranexamic acid group (p<0.001) Conclusion: Treatment with tranexamic acid reduced the median duration of hospital stay by two days. Statistically significant differences in mean International Normalized Ratio levels were seen at day 5 and 6 of hospitalization (p<0.001). BJHS 2018;3(1)5 : 346-349